Scratch-resistant wear-resistant anti-burst UV oil and preparation method thereof
By combining prepolymers, hard UV monomers and flexible UV monomers in UV varnish, a three-dimensional crosslinked structure is formed and modified silicone vesicles are added, the problem of insufficient scratch resistance and wear resistance of existing UV varnish is solved, and a high-performance UV oil coating is achieved.
Patent Information
- Application Number
- CN202411860316.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-28
AI Technical Summary
The existing UV varnishing oil has insufficient scratch resistance and wear resistance during the transportation of paper printed materials and cannot replace the traditional film protection process.
A scratch-resistant, wear-resistant, explosion-proof UV oil is developed. By reasonably proportioning prepolymers, hard UV monomers and flexible UV monomers, a three-dimensional cross-linked structure with hard and flexible regions is formed, and modified silicone vesicles are added as wear-resistant additives.
The coating after UV light curing has excellent wear resistance and scratch resistance, while maintaining excellent flexibility and burst resistance. It can pass transportation tests without scratching, grinding, and bursting without using film protection.
Smart Images

Figure CN119529660A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyurethane coatings, and in particular to a scratch-resistant, wear-resistant, and explosion-resistant UV oil and a preparation method thereof. Background Art
[0002] At present, a lot of plastic films are used in the paper printing and packaging industry, especially in the paper packaging boxes of high-end goods. For example, the packaging boxes of high-end cosmetics, tobacco, alcohol, electronic digital products, etc., some of them are covered with a layer of PET aluminum-coated film before printing, and some are attached with a layer of BOPP film after printing. In addition, in order to prevent scratches and abrasions caused by strong collisions during transportation, a layer of transparent film is wrapped outside the packaging box.
[0003] As the world pays more and more attention to environmental protection, resource conservation and recycling, all countries have introduced laws and regulations on plastic restriction. In the field of paper packaging, the elimination of film has become a development trend. There are two main types of surface treatment varnishes for paper printing and packaging, one is water-based varnish, and the other is ultraviolet curing (UV) varnish. The characteristics of water-based varnish are environmental protection, low odor, easy to use, and good flexibility, but it also has disadvantages such as poor wear and scratch resistance, low gloss, and poor solvent resistance. The characteristics of UV oil are fast curing and drying, good wear resistance, high gloss, and good solvent resistance, but it also has the characteristics of poor flexibility and easy cracking. Since the thickness of the varnish coating on paper printing is only 3-6 microns, the oxygen inhibition effect of ultraviolet curing is obvious in the case of thin coating. The scratch and wear resistance of all paper printing UV varnish is not very good. It cannot pass the vibration and friction during transportation. After long-distance transportation, there are more surface scratches. At present, it cannot achieve the effect of film protection.
[0004] Therefore, in this field, it is expected to develop a high-performance UV oil with ultra-high scratch resistance and excellent flexibility, so as to achieve the effect of no scratches, no abrasions, and no cracks in transportation tests without film protection, so as to replace the film protection process. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an anti-scratch, wear-resistant and anti-cracking UV oil, which comprises, by mass percentage:
[0006] Prepolymer: 35-45%,
[0007] Hardness UV monomer: 25-35%,
[0008] Flexible UV monomer: 10-25%,
[0009] Photoinitiator: 3-8%,
[0010] Wear-resistant additive: 1-3%,
[0011] Defoaming agent: 0.1-5%,
[0012] Leveling agent: 0.1-1%.
[0013] The prepolymer includes one or more of aliphatic trifunctional polyurethane acrylate, aliphatic hexafunctional polyurethane acrylate, aromatic trifunctional polyurethane acrylate, and aromatic hexafunctional polyurethane acrylate;
[0014] The hard UV monomer includes one or more of dipentaerythritol hexaacrylate, 2 moles of caprolactone-modified dipentaerythritol hexaacrylate, and 6 moles of caprolactone-modified dipentaerythritol hexaacrylate;
[0015] The flexible UV monomer includes one or more of dicyclotrimethylolpropane methylal acrylate, dicyclopentenyl ethoxylated acrylate, stearic acid methacrylate, tripropylene glycol diacrylate, and ethoxylated (6) trimethylolpropane triacrylate.
[0016] Furthermore, the photoinitiator includes one or more of 4-chlorobenzophenone, 4-methylbenzophenone, methyl benzoylformate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexylphenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, and active amines.
[0017] Furthermore, the wear-resistant additive includes an ultrafine microsphere wear-resistant and anti-scratch additive, which refers to one or more of nylon 12 microsphere powder, PMMA microsphere powder, silicone microsphere powder, and modified silicone vesicles.
[0018] Furthermore, the wear-resistant additive is a modified silicone vesicle, the modified silicone vesicle is an oil-in-water structure, the outer layer of the modified silicone vesicle is a hydrophilic group, the hydrophilic group is in-situ grafted with methyl acrylate, and the molar ratio of the modified silicone vesicle to the grafted methyl acrylate is greater than 1:1.
[0019] Furthermore, the diameter of the modified organosilicon vesicles is greater than 550 nm.
[0020] The present invention also provides a method for preparing anti-scratch, wear-resistant and anti-cracking UV oil, comprising the following steps:
[0021] Adding prepolymer, hard UV monomer and flexible UV monomer into a stirring container in sequence at room temperature, and performing a first stirring;
[0022] Adding a photoinitiator and a defoamer into the stirring container and performing a second stirring;
[0023] Perform the third stirring, add the wear-resistant additive and the leveling agent into the stirring container at the same time, and then perform the fourth stirring;
[0024] After filtering and packaging, the anti-scratch, wear-resistant and anti-cracking UV oil is obtained.
[0025] Furthermore, the stirring speed of the first stirring is 300-500r / min, and the stirring time of the first stirring is 30 minutes; the stirring speed of the second stirring is 500-800r / min, and the stirring time of the second stirring is 1-2 hours; the stirring speed of the third stirring is 100-200r / min; the stirring speed of the fourth stirring is 500-800r / min, and the stirring time of the fourth stirring is 30 minutes.
[0026] Further, the prepolymer includes one or more of aliphatic trifunctional polyurethane acrylate, aliphatic hexafunctional polyurethane acrylate, aromatic trifunctional polyurethane acrylate, and aromatic hexafunctional polyurethane acrylate;
[0027] The hard UV monomer includes one or more of dipentaerythritol hexaacrylate, 2 moles of caprolactone-modified dipentaerythritol hexaacrylate, and 6 moles of caprolactone-modified dipentaerythritol hexaacrylate;
[0028] The flexible UV monomer includes one or more of dicyclotrimethylolpropane methylal acrylate, dicyclopentenyl ethoxylated acrylate, stearic acid methacrylate, tripropylene glycol diacrylate, and ethoxylated (6) trimethylolpropane triacrylate.
[0029] Furthermore, the wear-resistant additive is a modified silicone vesicle, the modified silicone vesicle is an oil-in-water structure, the outer layer of the modified silicone vesicle is a hydrophilic group, and the hydrophilic group is in-situ grafted with methyl acrylate.
[0030] Furthermore, the preparation method of the wear-resistant additive comprises:
[0031] Based on glycerol and methyl methacrylate, aminopropyltriethoxysilane is grafted and modified to obtain a modified silane including a hydrophilic group and a hydrophobic group, and the molar ratio of the modified silane, the hydrophilic group and the hydrophobic group is (0.9-1.1): (0.9-1.1): (0.9-1.1);
[0032] By high shear emulsification, the modified silane is used as a raw material to prepare organosilicon vesicles;
[0033] Based on methyl acrylate, the hydrophilic group of the silicone vesicle is grafted and modified to obtain a modified silicone vesicle as a wear-resistant additive, wherein the molar ratio of the modified silicone vesicle to the grafted methyl acrylate is greater than 1:1.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. By mixing hard UV monomers and flexible UV monomers into prepolymers, the UV-cured coating not only has excellent wear resistance but also has strong flexibility.
[0036] 2. By using modified silicone vesicles as wear-resistant additives, the modified silicone vesicles can float in the anti-cracking UV varnish and be fixed on the surface of the cured film layer to prevent the cured film layer from being scratched. It can also provide a buffer for the friction of the force-applying object, further improving the wear resistance of the cured film layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 This is a schematic diagram of the structure formed by the prepolymer, hard UV monomer and flexible UV monomer provided by the present invention after UV light curing;
[0039] Figure 2 A schematic diagram of the state of the modified organic silicon vesicles provided by the present invention on the surface of the cured film layer after photocuring;
[0040] Figure 3 This is a schematic diagram of the state of the solidified film layer provided by the present invention when it is rubbed by a force-applying object. DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0043] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not indicated in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, if not otherwise specified, can all be obtained from commercial channels).
[0044] The present invention provides a scratch-resistant, wear-resistant and crack-resistant UV oil, which comprises, by mass percentage:
[0045] Prepolymer: 35-45%,
[0046] Hardness UV monomer: 25-35%,
[0047] Flexible UV monomer: 10-25%,
[0048] Photoinitiator: 3-8%,
[0049] Wear-resistant additive: 1-3%,
[0050] Defoaming agent: 0.1-5%,
[0051] Leveling agent: 0.1-1%.
[0052] The prepolymer includes one or more of aliphatic trifunctional polyurethane acrylate, aliphatic hexafunctional polyurethane acrylate, aromatic trifunctional polyurethane acrylate, and aromatic hexafunctional polyurethane acrylate;
[0053] The hard UV monomer includes one or more of dipentaerythritol hexaacrylate, 2 moles of caprolactone-modified dipentaerythritol hexaacrylate, and 6 moles of caprolactone-modified dipentaerythritol hexaacrylate;
[0054] The flexible UV monomer includes one or more of dicyclotrimethylolpropane methylal acrylate, dicyclopentenyl ethoxylated acrylate, stearic acid methacrylate, tripropylene glycol diacrylate, and ethoxylated (6) trimethylolpropane triacrylate.
[0055] The prepolymer acts as the main chain of the network during the cross-linking process, providing basic physical and mechanical properties. The hard UV monomer contains multiple rigid ring structures, benzene rings or other rigid groups. These structures restrict the rotation and bending of the molecules, thereby forming rigid regions in the cross-linked network; while the flexible UV monomer contains long-chain alkyl, ethoxy groups or other flexible chain segments. The intermolecular forces are relatively weak, allowing the polymer chain to have greater freedom of movement and rotation, thereby giving the material flexibility and elasticity.
[0056] Figure 1The structure formed by the prepolymer, hard UV monomer and flexible UV monomer after UV light curing is shown.
[0057] For example, in Figure 1 In the figure, the prepolymer is represented by a circle, the hard UV monomer is represented by a square, and the flexible UV monomer is represented by a triangle. Due to the characteristics of the hard UV monomer and the flexible UV monomer, other monomers connected around the hard UV monomer will form a rigid hard zone with the hard UV monomer, and other monomers connected around the flexible UV monomer will form an elastic flexible zone with the flexible UV monomer. When the formed cross-linked structure is subjected to external friction, the hard zone will resist the external force to prevent the surface of the cured coating from being scratched; when the formed cross-linked structure is subjected to tensile or extrusion force, the flexible zone will buffer the external force through its elastic structure to prevent the entire coating from breaking.
[0058] By mixing hard UV monomers and flexible UV monomers into the prepolymer, the UV light-cured coating not only has excellent wear resistance but also has strong flexibility.
[0059] Furthermore, the photoinitiator includes one or more of 4-chlorobenzophenone, 4-methylbenzophenone, methyl benzoylformate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexylphenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, and active amines.
[0060] Furthermore, the wear-resistant additive includes an ultrafine microsphere wear-resistant and anti-scratch additive, which refers to one or more of nylon 12 microsphere powder, PMMA microsphere powder, silicone microsphere powder, and modified silicone vesicles.
[0061] Furthermore, the wear-resistant additive is a modified silicone vesicle, the modified silicone vesicle is an oil-in-water structure, the outer layer of the modified silicone vesicle is a hydrophilic group, the hydrophilic group is in-situ grafted with methyl acrylate, and the molar ratio of the modified silicone vesicle to the grafted methyl acrylate is greater than 1:1.
[0062] The modified silicone vesicles adopt a water-in-oil (W / O) structure, with a hydrophobic oil phase in the inner core and a hydrophilic group coated on the outer layer. This allows the modified silicone vesicles to be stably dispersed in the UV varnish system, preventing aggregation or precipitation due to poor compatibility. The hydrophilic groups on the outer layer improve the dispersibility and uniformity of the vesicles in the varnish, helping to form a stable nano-scale dispersion system.
[0063] By in-situ grafting of methyl acrylate (MA) on the hydrophilic group, double bonds (C=C) with photocurable crosslinking ability were introduced into the surface of the modified silicone vesicles. Only one MA molecule was grafted on the surface of each vesicle, so that the modified silicone vesicles could form a balloon-like structure.
[0064] Furthermore, the diameter of the modified organosilicon vesicles is greater than 550 nm.
[0065] In order to ensure that the modified silicone vesicles can float to the surface of the UV varnish after coating and achieve the purpose of improving the surface wear resistance, it is necessary to control the density of the silicone vesicles to be lower than that of the UV varnish. The calculation process is as follows:
[0066] The organosilicon vesicle is a hollow spherical structure with an outer radius of R and a shell thickness of t. The average density of the vesicle is vesicle It can be calculated by the following formula:
[0067]
[0068] Among them, the vesicle mass m is mainly composed of the mass of the shell material, the vesicle volume V is the volume of the entire sphere, and the calculation formula of the vesicle mass m is:
[0069] m = shell volume × ρ shell =4πR 2 t×ρ shell
[0070] Where t is the shell thickness, R is the shell outer diameter, ρ shell is the shell density;
[0071] The calculation formula of vesicle volume V is:
[0072]
[0073] Where R is the outer diameter of the shell.
[0074] Therefore, the average density formula is:
[0075]
[0076] Among them, ρ vesicle is the average density of the vesicles, t is the shell thickness, R is the outer diameter of the shell, ρ shell is the shell density.
[0077] In order to achieve the floating effect, the following conditions must be met:
[0078] ρ vesicle <ρ varnish
[0079] Among them, ρ varnish is the average density of UV varnish.
[0080] Substituting into the average density formula we get:
[0081]
[0082] Substituting typical data, the average density of anti-cracking UV varnish ρ varnish : 1.2g / cm 3 , the density of the shell material ρ shell : 2.2g / cm 3 , shell thickness t is: 50nm, calculate the outer radius R:
[0083]
[0084] Therefore, the outer radius R must be larger than 0.275 μm, that is, the diameter of the vesicle must be larger than 550 nm.
[0085] Figure 2 The state of the modified silicone vesicles on the surface of the cured film layer after photocuring is shown.
[0086] like Figure 2 As shown, since the average density of the modified silicone vesicles is less than the average density of the UV varnish, after the UV varnish is applied on the base layer (e.g., paper products), the modified silicone vesicles can float to the surface of the coating. When the coating is irradiated with UV light, the coating is cross-linked and cured to form a cured film layer. At the same time, the methyl acrylate grafted on the modified silicone vesicles also participates in the cross-linking and curing, and the modified silicone vesicles are fixed to the surface of the cured film layer through the graft. It is understandable that there will of course be modified silicone vesicles that fail to float successfully. These modified silicone vesicles will be fixed in the coating due to the curing of the coating, but since each modified silicone vesicle will only have one grafted methyl acrylate at most, even if the methyl acrylate participates in the cross-linking, it will not affect the performance of the coating.
[0087] Figure 3 It shows the state of the solidified film layer when it is rubbed by a force-applying object.
[0088] like Figure 3As shown in the figure, the modified silicone vesicles are in a convex state on the surface of the cured film layer. At the same time, due to the small amount of wear-resistant additive added and the tiny particle size of the modified silicone vesicles that is invisible to the naked eye, even if the modified silicone vesicles grow on the surface of the cured film layer, it will not affect the glossiness of the surface of the cured film layer. However, when the force-applying object squeezes the upper surface of the cured film layer and generates horizontal friction, the modified silicone vesicles are first subjected to the force. Due to the high hardness of the modified silicone vesicles, it is difficult for the cured film layer to contact the force-applying object, thereby preventing the cured film layer from being scratched. At the same time, the elastic grafts on the modified silicone vesicles will cause the modified silicone vesicles to produce a certain degree of elastic displacement in the force-applying direction, providing a buffer for the friction of the force-applying object, and further improving the wear resistance of the cured film layer.
[0089] The present application controls the diameter of the silicone vesicles, thereby controlling the average density of the silicone vesicles to be lower than the average density of the UV varnish, thereby allowing the silicone vesicles to float to the surface in the anti-cracking UV varnish, so that the high-hardness modified silicone vesicles can be subjected to force first, preventing the cured film layer from being scratched, and providing a buffer for the friction of the force-applying object, further improving the wear resistance of the cured film layer.
[0090] The present invention also provides a method for preparing anti-scratch, wear-resistant and anti-cracking UV oil, comprising the following steps:
[0091] S11, adding a prepolymer, a hard UV monomer and a flexible UV monomer into a stirring container in sequence at room temperature, and performing a first stirring;
[0092] S12, adding a photoinitiator and a defoamer into the stirring container, and performing a second stirring;
[0093] S13, performing a third stirring, adding a wear-resistant additive and a leveling agent to the stirring container at the same time, and then performing a fourth stirring;
[0094] S14, after filtering and packaging, the anti-scratch, wear-resistant and anti-cracking UV oil is obtained.
[0095] The anti-scratch, wear-resistant and anti-burst UV oil provided by the present invention forms a three-dimensional cross-linked structure with hard areas and flexible areas by reasonably mixing prepolymers, hard UV monomers and flexible UV monomers, which significantly improves the wear resistance and anti-scratch performance of the coating while maintaining excellent flexibility and anti-burst properties.
[0096] Further, in step S11, the stirring speed of the first stirring is 300-500r / min, and the stirring time of the first stirring is 30 minutes. In step S12, the stirring speed of the second stirring is 500-800r / min, and the stirring time of the second stirring is 1-2 hours. In step S13, the stirring speed of the third stirring is 100-200r / min; the stirring speed of the fourth stirring is 500-800r / min, and the stirring time of the fourth stirring is 30 minutes. In step S14, the filtration is performed using a 100-200 mesh filter bag.
[0097] By adopting precise control of steps S11 to S14, the preparation method of the present invention ensures the high quality and consistency of the anti-scratch, wear-resistant and anti-cracking UV oil, making the entire preparation process simple and efficient, the operating conditions controllable, and ensuring the high performance and stability of the product.
[0098] Further, the prepolymer includes one or more of aliphatic trifunctional polyurethane acrylate, aliphatic hexafunctional polyurethane acrylate, aromatic trifunctional polyurethane acrylate, and aromatic hexafunctional polyurethane acrylate;
[0099] The hard UV monomer includes one or more of dipentaerythritol hexaacrylate, 2 moles of caprolactone-modified dipentaerythritol hexaacrylate, and 6 moles of caprolactone-modified dipentaerythritol hexaacrylate;
[0100] The flexible UV monomer includes one or more of dicyclotrimethylolpropane methylal acrylate, dicyclopentenyl ethoxylated acrylate, stearic acid methacrylate, tripropylene glycol diacrylate, and ethoxylated (6) trimethylolpropane triacrylate.
[0101] The prepolymer serves as the main chain of the three-dimensional cross-linked structure, providing a solid physical and mechanical foundation; the hard UV monomer contains multiple rigid ring structures or benzene rings, which limit the rotation and bending of the molecules, form rigid areas, and enhance the wear and scratch resistance of the coating; the flexible UV monomer contains flexible chain segments such as long-chain alkyl and ethoxy groups, which give the polymer chain greater freedom of movement and rotation, thereby improving the flexibility and elasticity of the coating.
[0102] Furthermore, the wear-resistant additive is a modified organic silicon vesicle, the modified organic silicon vesicle is an oil-in-water structure, the outer layer of the modified organic silicon vesicle is a hydrophilic group, and the hydrophilic group is in-situ grafted with methyl acrylate. The preparation method of the wear-resistant additive includes:
[0103] S21, based on glycerol and methyl methacrylate, aminopropyltriethoxysilane is grafted and modified to obtain a modified silane including a hydrophilic group and a hydrophobic group, wherein the molar ratio of the modified silane, the hydrophilic group and the hydrophobic group is (0.9-1.1): (0.9-1.1): (0.9-1.1);
[0104] S22, preparing organosilicon vesicles by high shear emulsification using the modified silane as a raw material;
[0105] S23. Based on methyl acrylate, the hydrophilic group of the silicone vesicle is grafted and modified to obtain modified silicone vesicles as a wear-resistant additive, wherein the molar ratio of the modified silicone vesicles to the grafted methyl acrylate is greater than 1:1.
[0106] Step S21 is to prepare a modified silane including a hydrophilic group and a hydrophobic group. Further, step S21 includes:
[0107] S211. Add 100 mL of anhydrous ethanol as solvent into a dry flask.
[0108] S212. According to the molar amount of aminopropyltriethoxysilane (APTMS), anhydrous acetic acid is added as a catalyst, wherein the molar ratio of aminopropyltriethoxysilane to acetic acid is 1:1.5 (for example, if 1 mol of aminopropyltriethoxysilane is added, 1.5 mol of acetic acid is added accordingly).
[0109] S213, slowly add the mixed solution of aminopropyltriethoxysilane and acetic acid into the ethanol solution, control the reaction temperature at 40°C, control the stirring speed at 500 rpm, and stir for 2 hours to allow the aminopropyltriethoxysilane to be fully hydrolyzed to generate silanol groups.
[0110] S214. After the hydrolysis is completed, gradually add the hydrophilic group glycerol and the hydrophobic group methyl methacrylate (MMA) to the reaction mixture in step S214, and control the molar ratio of aminopropyltriethoxysilane, hydrophilic group and hydrophobic group to be (0.9-1.1): (0.9-1.1): (0.9-1.1), control the reaction temperature to 40°C, control the stirring speed to 500 rpm, and stir for 3 hours to evenly graft the hydrophilic group and the hydrophobic group to the silane molecules.
[0111] S215. After the reaction is completed, the solvent and unreacted low molecular weight substances are removed by vacuum distillation, the remaining modified silane solution is cooled to room temperature, and dried in a vacuum dryer to obtain modified silane.
[0112] The modified silane obtained in this step (S21) has a hydrophilic group and a hydrophobic group. When using it to prepare vesicles, it can be easily made into a vesicle shape by controlling the emulsifying solvent, thereby improving the emulsification effect.
[0113] Step S22 is to prepare organic silicon vesicles. Further, step S22 includes:
[0114] S221. In a dry container, add 25 g of modified silane prepared in S21, 35 g of caprylic acid triglyceride, and 15 g of anhydrous ethanol in sequence, and stir at 300 rpm for 10 minutes at room temperature to form a uniform hydrophobic phase mixture.
[0115] Among them, caprylic / decanoic acid triglyceride is used as a hydrophobic phase solvent, and anhydrous ethanol is used to reduce the viscosity of the hydrophobic phase and promote emulsification.
[0116] S222. In another container, add 100 g of deionized water, 3 g of polyoxyethylene sorbitan 80 (Tween 80), and 5 g of glycerol in sequence, and stir at room temperature at 200 rpm for 10 minutes to fully dissolve the surfactant and stabilizer.
[0117] Among them, polyoxyethylene sorbitan 80 is used as a surfactant and glycerol is used as a stabilizer.
[0118] S223, slowly drop the hydrophobic phase into the aqueous phase, and use a high shear emulsification device for high-speed stirring to perform an emulsification process, wherein the speed of the high shear emulsification is controlled to be 12,000 rpm, and the emulsification time is controlled to be 10 minutes.
[0119] S224. After emulsification is completed, the mixture is stirred at 25°C and 100 rpm for 30 minutes to make the vesicles more stable.
[0120] Since the target size of the vesicles is large, low shear emulsification should be used because it is easier to form larger vesicles. However, compared with low shear emulsification, the particle size of the vesicles obtained by high shear emulsification is more uniform. Therefore, by adjusting the emulsification parameters (such as shear rate, emulsification time, etc.), the vesicle size can be controlled to be larger than 0.55 microns even when high shear emulsification is used.
[0121] Specifically, dynamic light scattering (DLS) can be used to monitor the particle size in real time. When the particle size is too large, the shear rate of the high shear emulsification equipment is increased or the high shear emulsification time is extended, so that the particle size can be controlled to be larger than but as close to 0.55 μm as possible.
[0122] In this step (S22), the outer surface of the silicone vesicles obtained by emulsification has hydrophilic hydroxyl groups, so that the silicone vesicles can repel the hydrophobic UV varnish. The shear rate and emulsification time are also controlled to make the size of the silicone vesicles greater than 0.55 μm, thereby making the density of the silicone vesicles less than that of the UV varnish. Combining the above two points, the UV varnish to which the silicone vesicles (wear-resistant additive) prepared in the embodiment of the present application are added can, after coating, allow the silicone vesicles to float to the surface of the UV varnish, thereby obtaining a coating with a hard and wear-resistant surface. At the same time, the silicone vesicles dispersed on the surface do not cross-link with each other, so that the silicone vesicles on the surface do not affect the flexibility of the coating.
[0123] Step S23 is to modify the organosilicon vesicles. Further, step S23 includes:
[0124] S231. Weigh 10 g of modified organosilicon vesicles, add 200 mL of dimethylsulfamide (DMSO), and stir at 500 rpm for 10 minutes using a high-speed stirrer to disperse evenly.
[0125] S232. Weigh 0.5 g of catalyst methyl acrylate (DMC), slowly add it into the reaction system, and keep stirring at a rotation speed of 500 rpm.
[0126] S233, while maintaining the stirring speed at 500 rpm, slowly dropwise add methyl acrylate (MA), wherein the molar ratio of the silicone vesicles to the added methyl acrylate is 1:1.
[0127] S234, heating the reaction system to 60° C. and stirring at a stirring speed of 500 rpm for 4 hours to allow MA to fully react with the vesicle surface groups.
[0128] S235. After the reaction is completed, 200 mL of ethanol is added to terminate the reaction, and the mixture is cooled to room temperature to precipitate the modified vesicles. The mixture is then centrifuged at 3000 rpm for 30 minutes to separate the modified vesicles and remove the unreacted MA and catalyst.
[0129] S236. Ultrasonic cleaning of the modified vesicles with dimethylsulfamide for at least three times to remove residual reactants, and then drying the modified organosilicon vesicles under vacuum conditions to obtain modified organosilicon vesicles.
[0130] The surface of the modified silicone vesicles mainly includes amino groups (-NH2) and hydroxyl groups (-OH), which are formed by grafting aminopropyltriethoxysilane (APTES) with glycerol. During the grafting process, these functional groups serve as reaction sites.
[0131] The molecular structure of methyl acrylate (MA) contains a reactive allyl group (CH2=CH-COOCH3) and a carbonyl group (C=O). The allyl part of methyl acrylate is highly reactive and can participate in polymerization and cross-linking reactions under free radical conditions.
[0132] Dimethyl carbonate is added to the reaction system as a catalyst. Dimethyl carbonate decomposes under heating conditions to release free radicals (·CH3OCOO·). These free radicals attack the double bond (C=C) of the MA molecule to generate free radical intermediates of MA (·CH2-C·H-COOCH3). The free radical intermediates of MA are highly reactive and can react with amino or hydroxyl groups on the surface of the silicone vesicles: for hydroxyl groups, the free radical intermediates react with the hydroxyl groups to form ester bonds (-O-CO-CH3); for amino groups (-NH2), the free radical intermediates react with the amino groups to form amide bonds (-NH-CO-CH3).
[0133] When the modified silicone vesicles participate in the crosslinking and curing under UV light of UV varnish, the MA grafted groups (-O-CO-CH3 or -NH-CO-CH3) on the surface of the modified silicone vesicles generate new free radicals or participate in chain growth under the action of free radicals. The double bonds of these groups can react with other monomers or crosslinking groups to become the connection points of the crosslinking network.
[0134] By grafting a methyl acrylate functional group on the surface of the silicone vesicle, the modified silicone vesicle becomes a "balloon"-like structure. The methyl acrylate functional group can participate in the cross-linking and curing process of UV varnish under UV light, so that the modified silicone vesicle can float to the surface of the UV varnish and then be "bolted" on the coating surface by UV light irradiation, thereby enabling the modified silicone vesicle to grow firmly on the coating surface, further enhancing the wear resistance of the coating surface. In addition, when subjected to external forces, the silicone vesicle part on the modified silicone vesicle can provide a microscopic buffering effect due to the grafted long chain.
[0135] In the experiment, the supplier of reagents was Sigma-Aldrich; the model of high shear emulsification equipment was Silverson's L5M-A Homogenizer; the model of stirring equipment was IKA Werke's Stirrer RCT Basic; the model of vacuum distillation apparatus was Büchi's Büchi R-200; the model of vacuum dryer was Varian's Varian Multivac RVCVacuum Oven; the model of microfiltration equipment was Millipore's Express PLUS Membrane Filters; the model of particle size analyzer was Malvern Panalytical's Mastersizer 3000; the model of centrifugal equipment was Eppendorf 5424 centrifuge; the model of ultrasonic cleaning equipment was Branson 5800.
[0136] Example 1
[0137] This embodiment provides a method for preparing a scratch-resistant, wear-resistant, and crack-resistant UV oil, which specifically comprises the following steps:
[0138] S1. Weigh the raw materials according to the following mass percentages:
[0139] Aliphatic trifunctional polyurethane acrylate 43%, dipentaerythritol hexaacrylate 34%, cyclotrimethylolpropane formal acrylate 15%, 1-hydroxy-cyclohexyl phenyl ketone 6%, wear-resistant additive AP-5E 1.2%, defoaming agent Airex900 0.2%, leveling agent Glide432 0.6%.
[0140] S2. At room temperature, add prepolymer aliphatic trifunctional polyurethane acrylate, hard UV monomer dipentaerythritol hexaacrylate and flexible UV monomer cyclotrimethylolpropane formal acrylate into a stirring tank in sequence, stir for 30 minutes at a stirring speed of 300-500r / min to allow the three to be fully mixed.
[0141] S3. Add photoinitiator 1-hydroxy-cyclohexyl phenyl ketone and defoamer into the mixing tank. Airex900, stirring speed is 500-800r / min, stirring and dispersing for 1-2 hours, stirring until the photoinitiator is completely dissolved.
[0142] S4. Reduce the stirring speed to 100-200r / min, and then add wear-resistant additives to the mixing tank. AP-5E and leveling agent Glide432, stirring and dispersing at a stirring speed of 500-800r / min for 30 minutes.
[0143] S5. Finally, filter and package with a 120-mesh filter bag to obtain anti-scratch, wear-resistant and anti-explosion UV oil.
[0144] S6. Coating performance test
[0145] The highly scratch-resistant, abrasion-resistant and crack-resistant UV varnish prepared in Example 1 was applied to the paper printed with the ink using a 6-micron coater at an energy of 80 mJ / cm 2 The coating properties are tested by UV curing, including appearance, viscosity, gloss, scratch resistance, wear resistance and flexibility.
[0146] Coating performance tests specifically include:
[0147] 6.1 Appearance: Visual inspection
[0148] 6.2 Viscosity: Use Tu-4 cup and test according to the requirements of viscosity cup in GB / T1723-1993.
[0149] 6.3 Gloss: Measured in accordance with GB / T9754, with an incident angle of 60 degrees
[0150] 6.4 Scratch resistance: Use a friction tester to test. Under a pressure of 4 pounds, rub the varnished surface against the varnished surface. The number of scratches when the two surfaces start to scratch indicates the scratch resistance.
[0151] 6.5 Abrasion resistance: Use a friction tester to test. Under a pressure of 4 pounds, the varnish surface is rubbed against A4 printing paper. The abrasion resistance is expressed by the number of times the coating film wears off the ink.
[0152] 6.6 Flexibility: The number of times the paint film begins to crack when it is folded in half.
[0153] Example 2
[0154] This embodiment provides a method for preparing a scratch-resistant, wear-resistant, and crack-resistant UV oil, which specifically comprises the following steps:
[0155] S1. Weigh the raw materials according to the following mass percentages:
[0156] Aliphatic hexafunctional polyurethane acrylate 40%, 2 mol caprolactone modified dipentaerythritol hexaacrylate 30%, cyclotrimethylolpropane formal acrylate 23%, 1-hydroxy-cyclohexyl phenyl ketone 5%, wear-resistant additive AP-5E 1.2%, defoaming agent Airex900 0.2%, leveling agent Glide 43 20.6%.
[0157] S2. At room temperature, add the prepolymer aliphatic hexafunctional polyurethane acrylate, the hard UV monomer 2 mol caprolactone modified dipentaerythritol hexaacrylate and the flexible UV monomer cyclotrimethylolpropane formal acrylate into the stirring tank in sequence, stir for 30 minutes at a stirring speed of 300-500r / min to allow the three to be fully mixed.
[0158] S3. Add photoinitiator 1-hydroxy-cyclohexyl phenyl ketone and defoamer into the mixing tank. Airex900, stirring speed is 500-800r / min, stirring and dispersing for 1-2 hours, stirring until the photoinitiator is completely dissolved.
[0159] S4. Reduce the stirring speed to 100-200r / min, and then add wear-resistant additives to the mixing tank. AP-5E and leveling agent Glide432, stirring and dispersing at a stirring speed of 500-800r / min for 30 minutes.
[0160] S5. Finally, filter and package with a 120-mesh filter bag to obtain anti-scratch, wear-resistant and anti-explosion UV oil.
[0161] S6. Coating performance test
[0162] The highly scratch-resistant, wear-resistant and crack-resistant UV varnish prepared in Example 2 was applied on the paper printed with the ink using a 6-micron coater and an energy of 80 mJ / cm 2 The coating properties are tested by UV curing, including appearance, viscosity, gloss, scratch resistance, wear resistance and flexibility.
[0163] Coating performance tests specifically include:
[0164] 6.1 Appearance: Visual inspection
[0165] 6.2 Viscosity: Use Tu-4 cup and test according to the requirements of viscosity cup in GB / T1723-1993.
[0166] 6.3 Gloss: Measured in accordance with GB / T9754, with an incident angle of 60 degrees
[0167] 6.4 Scratch resistance: Use a friction tester to test. Under a pressure of 4 pounds, rub the varnished surface against the varnished surface. The number of scratches when the two surfaces start to scratch indicates the scratch resistance.
[0168] 6.5 Abrasion resistance: Use a friction tester to test. Under a pressure of 4 pounds, the varnish surface is rubbed against A4 printing paper. The abrasion resistance is expressed by the number of times the coating film wears off the ink.
[0169] 6.6 Flexibility: The number of times the paint film begins to crack when it is folded in half.
[0170] Example 3
[0171] This embodiment provides a method for preparing a scratch-resistant, wear-resistant, and crack-resistant UV oil, which specifically comprises the following steps:
[0172] S1. Weigh the raw materials according to the following mass percentages:
[0173] Aliphatic trifunctional polyurethane acrylate 40%, 2 mol caprolactone modified dipentaerythritol hexaacrylate 32%, ethoxylated (6) trimethylolpropane triacrylate 21%, 1-hydroxy-cyclohexyl phenone 5%, wear-resistant additive AP-5E 1.2%, defoaming agent Airex900 0.2%, leveling agent Glide 43 20.6%.
[0174] S2. At room temperature, add the prepolymer aliphatic trifunctional polyurethane acrylate, the hard UV monomer 2 mol caprolactone modified dipentaerythritol hexaacrylate and the flexible UV monomer ethoxylated (6) trimethylolpropane triacrylate into a stirring tank in sequence, stir for 30 minutes at a stirring speed of 300-500 r / min to allow the three to be fully mixed.
[0175] S3. Add photoinitiator 1-hydroxy-cyclohexyl phenyl ketone and defoamer into the mixing tank. Airex900, stirring speed is 500-800r / min, stirring and dispersing for 1-2 hours, stirring until the photoinitiator is completely dissolved.
[0176] S4. Reduce the stirring speed to 100-200r / min, and then add wear-resistant additives to the mixing tank.
[0177] AP-5E and leveling agent Glide432, stirring and dispersing at a stirring speed of 500-800r / min for 30 minutes.
[0178] S5. Finally, filter and package with a 120-mesh filter bag to obtain anti-scratch, wear-resistant and anti-cracking UV oil.
[0179] S6. Coating performance test
[0180] The highly scratch-resistant, wear-resistant and crack-resistant UV varnish prepared in Example 3 was coated on the paper printed with the ink using a 6-micron coater and an energy of 80 mJ / cm 2 The coating properties are tested by UV curing, including appearance, viscosity, gloss, scratch resistance, wear resistance and flexibility.
[0181] Coating performance tests specifically include:
[0182] 6.1 Appearance: Visual inspection
[0183] 6.2 Viscosity: Use Tu-4 cup and test according to the requirements of viscosity cup in GB / T1723-1993.
[0184] 6.3 Gloss: Measured in accordance with GB / T9754, with an incident angle of 60 degrees
[0185] 6.4 Scratch resistance: Use a friction tester to test. Under a pressure of 4 pounds, rub the varnished surface against the varnished surface. The number of scratches when the two surfaces start to scratch indicates the scratch resistance.
[0186] 6.5 Abrasion resistance: Use a friction tester to test. Under a pressure of 4 pounds, the varnish surface is rubbed against A4 printing paper. The abrasion resistance is expressed by the number of times the coating film wears off the ink.
[0187] 6.6 Flexibility: The number of times the paint film begins to crack when it is folded in half.
[0188] Example 4
[0189] This embodiment provides a method for preparing a scratch-resistant, wear-resistant, and crack-resistant UV oil, which specifically comprises the following steps:
[0190] S1. Weigh the raw materials according to the following mass percentages:
[0191] Aliphatic trifunctional polyurethane acrylate 43%, dipentaerythritol hexaacrylate 34%, cyclotrimethylolpropane formal acrylate 15%, 1-hydroxy-cyclohexyl phenone 6%, wear-resistant additive modified silicone vesicle 1.2%, defoaming agent Airex900 0.2%, leveling agent Glide432 0.6%.
[0192] S2. At room temperature, add prepolymer aliphatic trifunctional polyurethane acrylate, hard UV monomer dipentaerythritol hexaacrylate and flexible UV monomer cyclotrimethylolpropane formal acrylate into a stirring tank in sequence, stir for 30 minutes at a stirring speed of 300-500r / min to allow the three to be fully mixed.
[0193] S3. Add photoinitiator 1-hydroxy-cyclohexyl phenyl ketone and defoamer into the mixing tank. Airex900, stirring speed is 500-800r / min, stirring and dispersing for 1-2 hours, stirring until the photoinitiator is completely dissolved.
[0194] S4. Reduce the stirring speed to 100-200r / min, and then add the wear-resistant additive modified silicone vesicles and leveling agent into the mixing tank. Glide432, stirring and dispersing at a stirring speed of 500-800r / min for 30 minutes.
[0195] S5. Finally, filter and package with a 120-mesh filter bag to obtain anti-scratch, wear-resistant and anti-explosion UV oil.
[0196] S6. Coating performance test
[0197] The highly scratch-resistant, wear-resistant and crack-resistant UV varnish prepared in Example 4 was coated on the paper printed with ink using a 6-micron coater and an energy of 80 mJ / cm 2 The coating properties are tested by UV curing, including appearance, viscosity, gloss, scratch resistance, wear resistance and flexibility.
[0198] Coating performance tests specifically include:
[0199] 6.1 Appearance: Visual inspection
[0200] 6.2 Viscosity: Use Tu-4 cup and test according to the requirements of viscosity cup in GB / T1723-1993.
[0201] 6.3 Gloss: Measured in accordance with GB / T9754, with an incident angle of 60 degrees
[0202] 6.4 Scratch resistance: Use a friction tester to test. Under a pressure of 4 pounds, rub the varnished surface against the varnished surface. The number of scratches when the two surfaces start to scratch indicates the scratch resistance.
[0203] 6.5 Abrasion resistance: Use a friction tester to test. Under a pressure of 4 pounds, the varnish surface is rubbed against A4 printing paper. The abrasion resistance is expressed by the number of times the coating film wears off the ink.
[0204] 6.6 Flexibility: The number of times the paint film begins to crack when it is folded in half.
[0205] Comparative Example 1
[0206] This comparative example provides a method for preparing a scratch-resistant, wear-resistant, and crack-resistant UV oil, which specifically comprises the following steps:
[0207] S1. Weigh the raw materials according to the following mass percentages:
[0208] Bisphenol A epoxy acrylate 55%, trimethylolpropane triacrylate 23%, tripropylene glycol diacrylate 15.2%, 1-hydroxy-cyclohexyl benzophenone 6%, defoamer Airex900 0.2%, leveling agent Glide 43 20.6%.
[0209] S2. At room temperature, add prepolymer bisphenol A epoxy acrylate, hard UV monomer trimethylolpropane triacrylate and flexible UV monomer tripropylene glycol diacrylate into a stirring tank in sequence, stir for 30 minutes at a stirring speed of 300-500r / min to allow the three to be fully mixed.
[0210] S3. Add photoinitiator 1-hydroxy-cyclohexyl phenyl ketone and defoamer into the mixing tank. Airex900, stirring speed is 500-800r / min, stirring and dispersing for 1-2 hours, stirring until the photoinitiator is completely dissolved.
[0211] S4. Reduce the stirring speed to 100-200r / min, and then add leveling agent to the mixing tank. Glide432, stirring and dispersing at a stirring speed of 500-800r / min for 30 minutes.
[0212] S5. Finally, filter and package with a 120-mesh filter bag to obtain universal wear-resistant UV oil.
[0213] S6. Coating performance test
[0214] The universal wear-resistant UV oil of comparative example 1 was applied on the paper with printing ink using a 6-micron coater and an energy of 80 mJ / cm 2 The coating properties are tested by UV curing, including appearance, viscosity, gloss, scratch resistance, wear resistance and flexibility.
[0215] Coating performance tests specifically include:
[0216] 6.1 Appearance: Visual inspection
[0217] 6.2 Viscosity: Use Tu-4 cup and test according to the requirements of viscosity cup in GB / T1723-1993.
[0218] 6.3 Gloss: Measured in accordance with GB / T9754, with an incident angle of 60 degrees
[0219] 6.4 Scratch resistance: Use a friction tester to test. Under a pressure of 4 pounds, rub the varnished surface against the varnished surface. The number of scratches when the two surfaces start to scratch indicates the scratch resistance.
[0220] 6.5 Abrasion resistance: Use a friction tester to test. Under a pressure of 4 pounds, the varnish surface is rubbed against A4 printing paper. The abrasion resistance is expressed by the number of times the coating film wears off the ink.
[0221] 6.6 Flexibility: The number of times the paint film begins to crack when it is folded in half.
[0222] Experimental Results
[0223] Table 1 Coating performance test results
[0224]
[0225] From the coating performance test results in Table 1, it can be concluded that in Examples 1-3 of the present application, by mixing hard UV monomers and flexible UV monomers into prepolymers, the UV light-cured coatings not only have excellent wear resistance but also strong flexibility. In Example 4 of the present application, by using modified organic silicone vesicles as wear-resistant additives, the modified organic silicone vesicles can float in the anti-explosion UV varnish and be fixed on the surface of the cured film layer, preventing the cured film layer from being scratched, and providing a buffer for the friction of the force-applying object, further improving the wear resistance of the cured film layer.
[0226] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. A scratch-resistant, wear-resistant and anti-cracking UV oil, characterized in that: In terms of mass percentage, it includes: Prepolymer: 35-45%, Hardness UV monomer: 25-35%, Flexible UV monomer: 10-25%, Photoinitiator: 3-8%, Wear-resistant additive: 1-3%, Defoaming agent: 0.1-5%, Leveling agent: 0.1-1%. The prepolymer includes one or more of aliphatic trifunctional polyurethane acrylate, aliphatic hexafunctional polyurethane acrylate, aromatic trifunctional polyurethane acrylate, and aromatic hexafunctional polyurethane acrylate; The hard UV monomer includes one or more of dipentaerythritol hexaacrylate, 2 moles of caprolactone-modified dipentaerythritol hexaacrylate, and 6 moles of caprolactone-modified dipentaerythritol hexaacrylate; The flexible UV monomer includes one or more of dicyclotrimethylolpropane methylal acrylate, dicyclopentenyl ethoxylated acrylate, stearic acid methacrylate, tripropylene glycol diacrylate, and ethoxylated (6) trimethylolpropane triacrylate.
2. The anti-scratch, wear-resistant and anti-cracking UV oil according to claim 1, characterized in that: The photoinitiator includes one or more of 4-chlorobenzophenone, 4-methylbenzophenone, methyl benzoylformate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexylphenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylethylphosphonate, and active amines.
3. The anti-scratch, wear-resistant and anti-cracking UV oil according to claim 1, characterized in that: The wear-resistant additive includes an ultrafine microsphere wear-resistant and anti-scratch additive, which refers to one or more of nylon 12 microsphere powder, PMMA microsphere powder, organic silicon microsphere powder, and modified organic silicon vesicles.
4. The anti-scratch, wear-resistant and anti-cracking UV oil according to claim 3, characterized in that: The wear-resistant additive is a modified silicone vesicle, which is an oil-in-water structure. The outer layer of the modified silicone vesicle is a hydrophilic group, and the hydrophilic group is in-situ grafted with methyl acrylate. The molar ratio of the modified silicone vesicle to the grafted methyl acrylate is greater than 1:
1.
5. The anti-scratch, wear-resistant and anti-cracking UV oil according to claim 4, characterized in that: The diameter of the modified organic silicon vesicle is greater than 550 nm.
6. A method for preparing a scratch-resistant, wear-resistant and anti-cracking UV oil, characterized in that: The following steps are involved: Adding prepolymer, hard UV monomer and flexible UV monomer into a stirring container in sequence at room temperature, and performing a first stirring; Adding a photoinitiator and a defoamer into the stirring container and performing a second stirring; Perform the third stirring, add the wear-resistant additive and the leveling agent into the stirring container at the same time, and then perform the fourth stirring; After filtering and packaging, the anti-scratch, wear-resistant and anti-cracking UV oil is obtained.
7. The method for preparing the anti-scratch, wear-resistant and anti-cracking UV oil according to claim 6, characterized in that: The stirring speed of the first stirring is 300-500r / min, and the stirring time of the first stirring is 30 minutes; the stirring speed of the second stirring is 500-800r / min, and the stirring time of the second stirring is 1-2 hours; the stirring speed of the third stirring is 100-200r / min; the stirring speed of the fourth stirring is 500-800r / min, and the stirring time of the fourth stirring is 30 minutes.
8. The method for preparing the anti-scratch, wear-resistant and anti-cracking UV oil according to claim 7, characterized in that: The prepolymer includes one or more of aliphatic trifunctional polyurethane acrylate, aliphatic hexafunctional polyurethane acrylate, aromatic trifunctional polyurethane acrylate, and aromatic hexafunctional polyurethane acrylate; The hard UV monomer includes one or more of dipentaerythritol hexaacrylate, 2 moles of caprolactone-modified dipentaerythritol hexaacrylate, and 6 moles of caprolactone-modified dipentaerythritol hexaacrylate; The flexible UV monomer includes one or more of dicyclotrimethylolpropane methylal acrylate, dicyclopentenyl ethoxylated acrylate, stearic acid methacrylate, tripropylene glycol diacrylate, and ethoxylated (6) trimethylolpropane triacrylate.
9. The method for preparing the anti-scratch, wear-resistant and anti-cracking UV oil according to claim 8, characterized in that: The wear-resistant additive is a modified organic silicon vesicle, the modified organic silicon vesicle is an oil-in-water structure, the outer layer of the modified organic silicon vesicle is a hydrophilic group, and the hydrophilic group is in-situ grafted with methyl acrylate.
10. The method for preparing the anti-scratch, wear-resistant and anti-cracking UV oil according to claim 9, characterized in that: The preparation method of the wear-resistant additive comprises: Based on glycerol and methyl methacrylate, aminopropyltriethoxysilane is grafted and modified to obtain a modified silane including a hydrophilic group and a hydrophobic group, and the molar ratio of the modified silane, the hydrophilic group and the hydrophobic group is (0.9-1.1): (0.9-1.1): (0.9-1.1); By high shear emulsification, the modified silane is used as a raw material to prepare organosilicon vesicles; Based on methyl acrylate, the hydrophilic group of the silicone vesicle is grafted and modified to obtain a modified silicone vesicle as a wear-resistant additive, wherein the molar ratio of the modified silicone vesicle to the grafted methyl acrylate is greater than 1:1.
Citation Information
Patent Citations
Aqueous UV (ultraviolet) printing ink dispersed by utilizing vermiculate micelle system and preparation method thereof
CN102382504A
Ultraviolet-curing anti-film gloss oil and preparation method thereof
CN109266204A
Anti-dazzle anti-fingerprint wear-resistant hardening liquid with rubber hand feeling, and preparation method thereof
CN113683952A
High-wear-resistance UV sinking ink and preparation method thereof
CN116751482A
Blister ultraviolet curing anti-fouling hardened coating as well as preparation method and application thereof
CN117327445A